Archaeal isoprenoid biosynthesis - Liman, Lie Stefanus Geraldy, author; Santangelo, Thomas, advisor; Laybourn, Paul, committee member; Peebles, Christie, committee member (Colorado State University. Libraries, 2018)
Many high value natural products - including artemisinin, squalene, and farnesene – are isoprenoids. Efforts to commercially produce isoprenoids are often complicated by low concentrations of isoprenoid precursors and the toxicity of isoprenoids in common production platforms (i.e. bacteria and yeasts). Archaeal-based production platforms provide a potential solution to the precursor toxicity problems as archaea produce isoprenoids in large quantities to generate their unique membrane hydrocarbon chains. One roadblock to commercial archaeal isoprenoid production platforms is the uncharacterized pathway leading to isoprenoid precursor synthesis. This project details, genetically and biochemical, the first three steps in the proposed pathway of archaeal isoprenoid biosynthesis - from acetyl-CoA to mevalonate - in Thermococcus kodakarensis.
Keywords: isoprenoid; mevalonate; Archaea